2018
DOI: 10.1136/bmjopen-2017-017211
|View full text |Cite
|
Sign up to set email alerts
|

A new model of exercise referral scheme in primary care: is the effect on adherence to physical activity sustainable in the long term? A 15-month randomised controlled trial

Abstract: IntroductionStudies had not yet overcome the most relevant barriers to physical activity (PA) adherence. An exercise referral scheme (ERS) with mechanisms to promote social support might enhance adherence to PA in the long term.SettingA randomised controlled trial in 10 primary care centres in Spain.ObjectiveTo assess the effectiveness of a primary care-based ERS linked to municipal resources and enhancing social support and social participation in establishing adherence to PA among adults over a 15-month peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 39 publications
(41 reference statements)
1
56
1
6
Order By: Relevance
“…The HLC population comprises a heterogeneous group with multiple health challenges [ 22 , 50 , 51 , 60 ]. Although group-based interventions enhancing social support have been found effective to promote PA [ 61 ], tailoring group-based programs to suit all groups’ requirements is demanding [ 49 ]. Given the substantial psychological challenges among participants attending the HLC program [ 50 , 51 ], the staffs’ competence on how to promote socio-psychological health is of particular importance [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HLC population comprises a heterogeneous group with multiple health challenges [ 22 , 50 , 51 , 60 ]. Although group-based interventions enhancing social support have been found effective to promote PA [ 61 ], tailoring group-based programs to suit all groups’ requirements is demanding [ 49 ]. Given the substantial psychological challenges among participants attending the HLC program [ 50 , 51 ], the staffs’ competence on how to promote socio-psychological health is of particular importance [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…2; 3; 5; 6; 7; 8; 9. Norway (Kuehl et al, 2016) 3;5;9;10 3;5 6 2; 6 Germany (Tuakli-Wosornu et al, 2016) 1;3; 5; 10 1;3 1;2;5 2;8;9 EEUU (Martin-Payo et al, 2016) 3; 10. 5.…”
Section: Socioeconomicunclassified
“…Thus, a therapeutic approach based on the combination of PNE and PE can improve quality of life and disability, decreasing the pain intensity of patients with CMP and those suffering from chronic spinal pain (CSP). Different clinical trials and reviews have shown promising results combining PNE and PE [45,46,48,[62][63][64][65][66], but there is no consensus on the optimal dose of PNE or PE. These types of interventions, in which the patient is the active part of the treatment, are not performed and have been scarcely evaluated in primary care (PC).…”
Section: Introductionmentioning
confidence: 99%